Pengembangan Sistem Pendukung Keputusan Pemilihan Mitra Pada Badan Pusat Statistik Kabupaten Bireuen Menggunakan Metode Smart - Zulkifli Zulkifli; Iskandar Zulkarnaini (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2023)
Badan Pusat Statisitik (BPS) is a non-ministerial government agency charged with the task of ensuring the availability of data for use by both the government and the public. The data collection process carried out at Badan Pusat Statisitik (BPS) was carried out using various methods, one of which was a survey which involved collecting all existing sample data. The data collection process certainly requires more effort. Therefore, Badan Pusat Statisitik (BPS) uses partner services for the data collection process. Partners of Badan Pusat Statisitik (BPS) are members of the public who were recruited through a lengthy recruitment process starting from file selection, written tests to interviews. In the partner recruitment process, problems often occur due to several reasons, ranging from the length of the selection process, the crowd of applicants to the emergence of subjective judgments. Based on these problems, the authors try to develop a decision support system-based recruitment system to provide partner recommendations using the SMART calculation model. The results obtained are that the system built can be used for criteria and alternatives according to needs with the partner recruitment process at Badan Pusat Statisitik (BPS) of Bireuen Regency. The system built can rank 12 alternatives against 6 criteria according to weights that can be determined according to needs